Fungi associated with Hypothenemus hampei (Coleoptera: Curculionidae: Scolytinae) in Tabasco, Mexico. (2019)
In the state of Tabasco, Mexico, the coffee berry borer Hypothenemus hampei, was reported for the first time in 2004. Since then it has become the main insect pest of coffee in this area. The aim of the present study was to document the mycobiota associated to H. hampei adults in coffee plantations of three localities of Tabasco: Teapa, Tacotalpa and Huimanguillo. Coffee berries infested with the coffee berry borer were collected from the field and adults of H. hampei were extracted. The fungi that grew on the Scolytinae cadavers were isolated and identified using taxonomic keys. Two isolates of each morphological species were molecularly identified. A total of 74 isolates was obtained from the cuticle of H. hampei. Of them, 52 presented morphological affinity with Fusarium solani, five with F. oxysporum, five with F. verticillioides, one with Geotrichum candidum and 11 with Beauveria bassiana. The DNA sequences showed similarity with sequences found in GenBank, with homologies of 99 % and 100 %, which coincided with each morphological species. The most abundant species was F. solani (70.2 %), followed by B. bassiana (14.8 %). The species F. verticillioides and F. oxysporum represented each one, at 6.7 %, respectively. The least abundant was G. candidum (1.3 %). The findings of the species F. verticillioides and G. candidum are new reports of micromycetes fungi associated with H. hampei. This study contributes to the knowledge of the diversity of fungi associated with H. hampei.